FOXP1 abnormalities in lymphoma: Translocation breakpoint mapping reveals insights into deregulated transcriptional control - Goatly, A; Bacon, C; Nakamura, S; Ye, H; Kim, I; Brown, P; Ruskoné-Fourmestraux, A; Cervera, P; Streubel, B; Banham, A; Du, M (2008)
Deregulation of FOXP1 expression plays an important role in lymphoma development although the underlying molecular mechanism is poorly understood. FOXP1 is targeted by chromosome translocations in MALT lymphoma and diffuse large B-cell lymphoma, where high-level protein expression is associated with poor prognosis. Nonetheless, the incidence and nature of FOXP1 abnormalities at both the genetic and protein levels, and their correlation in these lymphomas are not well established. We investigated FOXP1 translocation, copy number change and protein expression in MALT lymphoma (n=321), MALT lymphoma with a diffuse large B-cell lymphoma component (59), nodal diffuse large B-cell lymphoma (64) and extranodal diffuse large B-cell lymphoma (151) by interphase fluorescence in situ hybridization and immunohistochemistry. FOXP1 translocation was found in eight MALT lymphomas and three MALT lymphomas with diffuse large B-cell lymphoma, with all positive cases originating in the stomach. In diffuse large B-cell lymphoma, the translocation was seen in 5 cases originating in the stomach (2), tonsil (1), large intestine (1) and lymph node (1). Immunoglobulin heavy chain gene was the translocation partner in 11 of the 16 positive cases. Fluorescence in situ hybridization mapping revealed FOXP1 breakpoints within the 5′ untranslated region of the gene (upstream of exon 6, the first coding exon of full-length FOXP1) in 14 cases, but downstream of exon 6 (most likely upstream of exon 8) in the remaining 2 cases. Three copies of the FOXP1 gene were observed in MALT lymphoma (17%), MALT lymphoma with diffuse large B-cell lymphoma (12%) and diffuse large B-cell lymphoma (32%), including cases with FOXP1 translocation (19%). Immunohistochemistry showed strong/moderate FOXP1 staining in all the cases with FOXP1 translocation. However, FOXP1 expression was independent of FOXP1 translocation or copy number changes. Our findings suggest that (1) FOXP1 translocation may disrupt the full-length FOXP1 transcript and lead to expression of FOXP1 transcript variants with alternate 5′ ends and (2) mechanisms other than translocation and copy number changes are also responsible for FOXP1 overexpression in lymphoma. © 2008 USCAP, Inc All rights reserved.